2016
DOI: 10.1093/molbev/msv350
|View full text |Cite|
|
Sign up to set email alerts
|

Convergent Substitutions in a Sodium Channel Suggest Multiple Origins of Toxin Resistance in Poison Frogs

Abstract: Complex phenotypes typically have a correspondingly multifaceted genetic component. However, the genotype-phenotype association between chemical defense and resistance is often simple: genetic changes in the binding site of a toxin alter how it affects its target. Some toxic organisms, such as poison frogs (Anura: Dendrobatidae), have defensive alkaloids that disrupt the function of ion channels, proteins that are crucial for nerve and muscle activity. Using protein-docking models, we predict that three major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
110
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 93 publications
15
110
3
Order By: Relevance
“…Combining data from previous work (Tarvin et al. ; Yuan and Wang ) and newly generated sequences, we amassed a dataset of SCN4A sequences from 147 individuals of 45 species (35 Dendrobatoids and 10 outgroups; Tables and ), including the five known species of Phyllobates (36 samples; 2–14 per species). Alkaloid profiles are available for 30 of the 35 dendrobatoids used (Table ), which allows us to confidently assume that at least among the species sequenced BTX secretion originated at the base of Phyllobates .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining data from previous work (Tarvin et al. ; Yuan and Wang ) and newly generated sequences, we amassed a dataset of SCN4A sequences from 147 individuals of 45 species (35 Dendrobatoids and 10 outgroups; Tables and ), including the five known species of Phyllobates (36 samples; 2–14 per species). Alkaloid profiles are available for 30 of the 35 dendrobatoids used (Table ), which allows us to confidently assume that at least among the species sequenced BTX secretion originated at the base of Phyllobates .…”
Section: Methodsmentioning
confidence: 99%
“…; Santos and Cannatella ), and recent studies have identified amino acid substitutions on ion‐transport proteins targeted by these toxins that coincide phylogenetically with the origins of alkaloid sequestration (Tarvin et al. , ; Yuan and Wang ). Some of these changes have been shown to provide toxin resistance in vitro (Tarvin et al.…”
mentioning
confidence: 99%
“…It is unclear how common such pre-existing compensatory mutations are, although it appears that mutations providing incremental increases in resistance are quite common. In Danainae butterflies, newts, garter snakes, and poison frogs, toxin resistance tends to increase over evolutionary time via additional AA replacements that occur in parallel with increased concentrations of chemical defenses (15, 16, 34, 35). It is possible that pre-adaptive mutations that allow resistance to evolve with little cost are present in these organisms and simply have not been identified.…”
Section: Evolutionary Pathways Towards Epibatidine Resistancementioning
confidence: 99%
“…The Epipedobates, Ameerega , and Dendrobates ( Oophaga ) clades, which are evolutionarily young (6, 36), are an example of rapid and ongoing diversification possibly driven by the evolution of resistance to anti-predator toxins (15). We demonstrate that resistance to epibatidine involves finely tuning a highly conserved binding site without disrupting receptor function, providing insights into evolutionary pathways culminating in chemical defenses.…”
Section: Evolutionary Pathways Towards Epibatidine Resistancementioning
confidence: 99%
See 1 more Smart Citation